KRITIK SOSIAL MASALAH EKONOMI DALAM NOVEL TANAH PARA BANDIT KARYA TERE LIYE - Indah Nurmia Kusuma; Agung Pramujiono; Indayani (Jurnal Bastra (Bahasa dan Sastra), 2024)
This research aims to describe social critism of economic problems in the novel Tanah Para Bandit by Tere Liye. This research is based on the novel Tanah Para Bandit by Tere Liye, a story that raises the themes of caurage, friendship, and the spirit of fighting for justice. The novel Tanah Para Bandit by Tere Liye is very interesting to study using the theory of genetic structuralism because the novel contains criticism of social problems. This research method uses the hermeneutic method. The approach used is a descriptive approach. The data source for this research is the novel Tanah Para Bandit by Tere Liye. This research data is in the form of words, phrases or sentences that express aspects of social criticism of economic problems contained in the novel Tanah Para Bandit by Tere Liye. The data collection tecnique used in this research is in two stages, namely observation, and documents. The data analysis tecnique for this research are data reduction, data presentation, and conclusions. The results of this research indicate that the social criticism of economic problems in this research incudes; unemployment, poverty, corruption, value of money, profits, stealing, and debt.